Editorial: Lifespan Connectome Gradients for a Road to Mental Health - Zhou, Zi-Xuan; Zuo, Xi-Nian (Journal of the American Academy of Child and Adolescent Psychiatry, 2024)
The connectome, generally defined as a comprehensive map of the structural and/or functional connections of a complete set of neural elements, has been recognized to condense the mechanistic architecture of the brain and capture meaningful individual differences. Increasing efforts are being invested in exploring the associations between connectomes and behavior/symptoms to piece together guidelines from a systems/cognitive neuroscience perspective for reforming mental health care. This editorial sketches a road to mental health with lifespan connectome gradients (LCG), highlighting unique perspectives, prospects, and priorities.